Recessive Dystrophic Epidermolysis bullosa due to Hemizygous 40 kb Deletion of COL7A1 and the Proximate PFKFB4 Gene Focusing on the Mutation c.425A>G Mimicking Homozygous Status - Alfred Klausegger; Niklas Jeschko; Markus Grammer; Jan Cemper-Kiesslich; Franz Neuhuber; Anja Diem; Hannelore Breitenbach-Koller; Gabriele Sander; Dieter Kotzot; Johann Wolfgang Bauer; Martin Laimer (Diagnostics, 2022)
Background: Dystrophic Epidermolysis bullosa (DEB) is a rare inherited mechanobullous disease characterised by the hyperfragility of the skin and mucous membranes. It is (typically) caused by (loss-of-function) mutations in the COL7A1 gene that impair the formation of collagen type VII, which represents the major constituent of anchoring fibrils within the basement membrane zone of epithelialised tissues. In a 4-year-old patient diagnosed with the clinical features of recessive DEB, genotyping via Next-Generation EB Panel Sequencing initially revealed the homozygosity of the maternal c.425A>G mutation, while the paternal heterozygosity in exon 3 was lacking. This genetic profile suggested incongruent gene transmission due to uniparental isodisomy (UPD) or the occurrence of a hemizygous deletion of unknown size. Methods: Thus, the EB panel sequencing of genomic DNA, followed by a paternity test and analysis of microsatellite markers, as well as multiplex ligation-dependent probe amplification (MLPA) copy number analysis using patient and parental DNA, were performed. Results: This approach revealed a paternally derived hemizygous deletion spanning from exon 3 to exon 118. Linear amplification-mediated PCR (LAM-PCR) determined the breaking points within intron 2 of the COL7A1 gene, comprising a 40kb segment within intron 1 of the adjacent PFKFB4 gene. Conclusion: This report highlights the relevance of advanced molecular profiling to determine new/exceptional/unusual genotypes and the accurate mode of genetic transmission in DEB.